Միջարաբական տարաձայնություններն իրաքյան (2003թ.) պատերազմի շուրջ - Անդրանիկ Առաքելյան (ՀՀ ԳԱԱ հրատ.)
Иракская война, или Третья война в Персидском заливе, длилась с 20 марта 2003 по 15 декабря 2011 года. Военный конфликт начался с вторжения американских и союзных сил в Ирак с целью свержения режима Саддама Хусейна. The Iraq War, or the Third Gulf War, began on March 20, 2003, with the military invasion of Iraq by the United States of America and its allies to put an end to the Baath Party of Saddam Hussein, the fifth President of Iraq and a prominent leader of the Baath party in the Iraqi region.
Keywords: Modern History